Bilingual thematic dictionaries - Stark, M. P. (Martin P.) (Lexicographica. Series maior ;, 2011)
This book has three practical goals: to identify the characteristic features of the bilingual thematic dictionary (BTD), to gauge its usefulness, and to make suggestions as to how it could be improved. These aims are achieved by considering the lexicographic genres (bilingual, thematic, and pedagogical) which have been combined to create this hybrid reference work, carrying out textual analyses of contemporary thematic dictionaries, and employing three pieces of user research (a questionnaire, a test, and an experiment) to reveal learners' opinions and use of BTDs.